Effect of troglitazone on radiation sensitivity in cervix cancer cells - An, Zhengzhe (The Korean Society for Radiation Oncology, 2012)
PURPOSE: Troglitazone (TRO) is a peroxisome proliferator-activated receptor γ (PPARγ) agonist. TRO has antiproliferative activity on many kinds of cancer cells via G1 arrest. TRO also increases Cu(2+)/Zn(2+)-superoxide dismutase (CuZnSOD) and catalase. Cell cycle, and SOD and catalase may affect on radiation sensitivity. We investigated the effect of TRO on radiation sensitivity in cancer cells in vitro. MATERIALS AND METHODS: Three human cervix cancer cell lines (HeLa, Me180, and SiHa) were used. The protein expressions of SOD and catalase, and catalase activities were measured at 2-10 µM of TRO for 24 hours. Cell cycle was evaluated with flow cytometry. Reactive oxygen species (ROS) was measured using 2',7'-dichlorofluorescin diacetate. Cell survival by radiation was measured with clonogenic assay. RESULTS: By 5 µM TRO for 24 hours, the mRNA, protein expression and activity of catalase were increased in all three cell lines. G0-G1 phase cells were increased in HeLa and Me180 by 5 µM TRO for 24 hours, but those were not increased in SiHa. By pretreatment with 5 µM TRO radiation sensitivity was increased in HeLa and Me180, but it was decreased in SiHa. In Me180, with 2 µM TRO which increased catalase but not increased G0-G1 cells, radiosensitization was not observed. ROS produced by radiation was decreased with TRO. CONCLUSION: TRO increases radiation sensitivity through G0-G1 arrest or decreases radiation sensitivity through catalase-mediated ROS scavenging according to TRO dose or cell types. The change of radiation sensitivity by combined with TRO is not dependent on the PPARγ expression level.